2014
DOI: 10.1051/0004-6361/201424786
|View full text |Cite
|
Sign up to set email alerts
|

On the Raman O VI and related lines in classical novae

Abstract: We critically examine the recent claimed detection of Raman-scattered O VI at around 6830 Å in the iron curtain stage spectra of the classical CO nova V339 Del. The observed line variations are compatible in the profile and timing of emission line strength with an excited state transition of neutral carbon. Line formation in classical nova ejecta is physically very different from what it is in symbiotic binaries, in which the O VI emission line is formed within the wind of the companion red giant at low differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Nussbaumer et al (1989) and Schmid (1989) were the first to propose that an emission band at ∼6830 Å could be due to the Raman (1928) scattering of the O VI resonance doublet (1032/1038 Å) by neutral hydrogen. As Shore et al (2014) also point out, such Raman features are unlikely to be formed in the ejecta of MS-or SG-novae, but such features have been observed in the spectra of RG-novae (most notably, RS Oph; Joy & Swings 1945;Wallerstein & Garnavich 1986;Iijima 2009) and are common features of the wider group of symbiotic stars (Allen 1980). We note that the weaker Raman band at 7088 Å would be blended with the strong He I emission at 7065 Å.…”
Section: Multi-eruption Combined Visible Spectrummentioning
confidence: 54%
See 1 more Smart Citation
“…Nussbaumer et al (1989) and Schmid (1989) were the first to propose that an emission band at ∼6830 Å could be due to the Raman (1928) scattering of the O VI resonance doublet (1032/1038 Å) by neutral hydrogen. As Shore et al (2014) also point out, such Raman features are unlikely to be formed in the ejecta of MS-or SG-novae, but such features have been observed in the spectra of RG-novae (most notably, RS Oph; Joy & Swings 1945;Wallerstein & Garnavich 1986;Iijima 2009) and are common features of the wider group of symbiotic stars (Allen 1980). We note that the weaker Raman band at 7088 Å would be blended with the strong He I emission at 7065 Å.…”
Section: Multi-eruption Combined Visible Spectrummentioning
confidence: 54%
“…As noted by Shore et al (2014), a possible interpretation of this line is "simply" emission from C I (6830 Å), especially in CNe. However, we also note that other (typically stronger; see Kramida et al 2015) C I lines (e.g., 6014 and 7115 Å) are not seen in the combined spectrum.…”
Section: Multi-eruption Combined Visible Spectrummentioning
confidence: 87%
“…Four ionization stages were available for C (C • -C +3 ) (C I profiles from the earliest spectra are presented in Shore et al (2014) and de Gennaro Aquino et al (2015) and N (N + -N +4 ) during the epochs of simultaneous FIES and STIS coverage. This spectral development is shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been detected in the range γ-rays A&A 590, A123 (2016) (Ackermann et al 2014) through centimeter radio (ATel 5298,5376). A study of the carbon spectrum in V339 del was published in Shore et al (2014). A high resolution atlas of the first four months of the outburst, covering 3800−8800 Å, has been published by De Gennaro Aquino et al (2015) and a discussion of the infrared development by Gehrz et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…They determined the ejected mass to be a few × 10 −4 M . Skopal et al also reported the emergence of Raman-scattered O VI λ = 1032, 1038 Å at around 6825 Å (but see Shore et al 2014, for a more plausible counter-interpretation in terms of emission by C I). Shore et al (2016) have undertaken a multiwavelength study of V339 Del, including X-ray data obtained with Swift, UV with the Hubble Space Telescope and ground-based optical observations.…”
Section: 3 9 D E L P H I N Imentioning
confidence: 98%